Sedimentary and tectonic architecture of a large push moraine:A case study from Hagafellsjökull-Eystri, Iceland - Bennett, Matthew R.; Huddart, David; Waller, Richard I.; Cassidy, Nigel; Tomio, Alexandre; Zukowskyj, Paul; Midgley, Nicholas G.; Cook, Simon J.; Gonzalez, Silvia; Glasser, Neil F. (Sedimentary Geology, 2004)
Using a combination of geological and geophysical techniques (Ground Penetrating Radar), we explore the tectonic architecture of a push moraine formed just after the 1890 Neoglacial ice maximum of Hagafellsjökull-Eystri, in central Iceland. The push moraine formed by a re-advance, perhaps a surge, of the glacier against a moraine bank-delta sometime between 1890 and 1929. Different tectonic architectures exist in two adjacent parts of the same push moraine complex. In one location, the ice advance pushed the delta pro-glacially to form a prominent single-crested push moraine. Deformation occurred along a single listric décollement over which a large nappe moved, as a result of ice-marginal pushing. In an adjacent location, the ice-margin mounted and advanced over the ice-contact delta to create a push moraine at the limit of the advance by subglacial gravity-spreading. In this case, deformation occurred along a series of listric thrusts and by folding within the distal parts of the over-ridden delta. The geomechanical causes of these two contrasting styles of deformation, present in adjacent sectors of the same ice-marginal flow unit, are discussed and a range of possible controls identified. These include variation along the former ice-margin and foreland in: (1) glacier-foreland coupling; (2) foreland shear strength; and (3) the frictional characteristics of the décollement. Some combination of these variables provides the most likely cause. The case study presented in this paper provides an example of the potential for rapid variation in the tectonic architecture of a push moraine along strike.